Efektivitas Konseling Kelompok Sebagai Intervensi Psikologis untuk Mereduksi Resiliensi pada Generasi Z - Dwi Septia Ningsih; Lidiana Rahayu Ningsih; Della Dornauli Simanjuntak; Tria Yunita; Ratna Sari Dewi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This study aims to prove the effectiveness of group counseling services in increasing resilience in generation z. The method used was a literature study of 24 previous studies. The results showed that group counseling is effective in increasing resilience, especially in preparing and helping generation z face all kinds of challenges and competition in the era of the industrial revolution 5.0. The effectiveness of the service is influenced by group dynamics, the implementation of the counseling stages, and barriers such as shyness, anxiety, and time constraints. Various techniques have been used in group counseling, such as reality group counseling, assertive training, ego approach with self-management techniques, solution-focused brief counseling (SFBC), cognitive restructuring, and solution-focused brief therapy. It is concluded that group counseling services play a significant role in increasing generation z resilience if implemented with appropriate techniques and the right approach.